2020
DOI: 10.1101/2020.04.14.040782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The global population of SARS-CoV-2 is composed of six major subtypes

Abstract: 16The World Health Organization characterized the COVID-19 as a pandemic in March 2020, the second 17 pandemic of the 21 st century. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a 18 positive-stranded RNA betacoronavirus of the family Coronaviridae. Expanding virus populations, as 19 that of SARS-CoV-2, accumulate a number of narrowly shared polymorphisms imposing a 20 confounding effect on traditional clustering methods. In this context, approaches that reduce the 21 complexity of the se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…1a). This mutation with glycine at the residue 614 (G614) was previously detected to increase with an alarming speed 21,22 . Our own analysis of the S-protein sequences available from the GenBank showed a similar result: The G614 genotype was not detected in February (among 33 sequences) and observed at low frequency in March (26%), but increased rapidly by April (65%) and May (70%) (Fig.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…1a). This mutation with glycine at the residue 614 (G614) was previously detected to increase with an alarming speed 21,22 . Our own analysis of the S-protein sequences available from the GenBank showed a similar result: The G614 genotype was not detected in February (among 33 sequences) and observed at low frequency in March (26%), but increased rapidly by April (65%) and May (70%) (Fig.…”
mentioning
confidence: 94%
“…Recent analyses of the fine-scale sequence variation of SARS-CoV-2 isolates identified several genomic regions of increased genetic variation [21][22][23][24][25][26][27][28][29][30] . One of these variations encodes a S-protein mutation, D614G, in the carboxy(C)-terminal region of the S1 domain [21][22][23]26,30 . This region of the S1 domain directly associates with S2 ( Fig.…”
mentioning
confidence: 99%
“…A recent article showed retroviruses pseudotyped with Glycine at 614 position infected ACE2-expressing cells markedly more efficiently than those with Aspartic acid due to less S1 shedding & greater incorporation of the S protein into the pseudovirion 24 . Several studies reported D614G mutation is increasing at an alarming rate 25 , 26 . Few observed that this alteration correlated with increased viral loads in COVID-19 patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Morais Junior at al. [21] propose a subdivision of the global SARS-CoV2 population into sixteen subtypes, defined using "widely shared polymorphisms" identified in nonstructural (nsp3, nsp4, nsp6, 27 nsp12, nsp13 and nsp14) cistrons, structural (spike and nucleocapsid), and accessory (ORF8) genes. VCM supports all the information required to replicate the definition of such subtypes.…”
Section: Answering Complex Biological Queriesmentioning
confidence: 99%